2002
DOI: 10.1152/japplphysiol.00820.2001
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in lipoprotein lipase activity in rat skeletal muscles during denervation-reinnervation

Abstract: Ż ernicka, E., E. Smol, J. Langfort, and M. Gó recka. Time course of changes in lipoprotein lipase activity in rat skeletal muscles during denervation-reinnervation. J Appl Physiol 92: 535-540, 2002; 10.1152/japplphysiol.00820. 2001.-The effects of denervation-reinnervation after sciatic nerve crush on the activity of extracellular and intracellular lipoprotein lipase (LPL) were examined in the soleus and red portion of gastrocnemius muscles. The activity of both LPL fractions was decreased in the two muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…At 20 days we observed that muscles were reinnervated. This is in accord with other data indicating such a time course in the rat soleus and extensor digitorum longus muscle [30,31]. While at this time some restitution of the normal muscle MMP distribution was observed and zymography indicated that MMP activity was lower than that in the acute phase following denervation, MMP activity remained higher than that in normal muscle.…”
Section: Discussionsupporting
confidence: 91%
“…At 20 days we observed that muscles were reinnervated. This is in accord with other data indicating such a time course in the rat soleus and extensor digitorum longus muscle [30,31]. While at this time some restitution of the normal muscle MMP distribution was observed and zymography indicated that MMP activity was lower than that in the acute phase following denervation, MMP activity remained higher than that in normal muscle.…”
Section: Discussionsupporting
confidence: 91%
“…After transport into the cytoplasm, FA binds to the fatty acid binding protein 3 (FABP3). Both LPL and FABP3 have been shown to be highly sensitive to contractile activity in muscle [ 51 , 52 ]. Here, both Lpl and Fabp3 genes showed high sensitivity to SCI induced disuse and to locomotor training.…”
Section: Discussionmentioning
confidence: 99%
“…Denervation induces an immediate loss of skeletal muscle mass [36]. Although reinnervation after long-term denervation may result in the partial recovery of muscle mass, it is typically not restored to the original state [37]. A recent study showed that signaling by bone morphogenetic proteins (BMPs) strongly exacerbated the effects of denervation and fasting [38].…”
Section: Discussionmentioning
confidence: 99%